Water Polo Players of Montenegro and Serbia who participated in the FINA World Junior Water Polo Championship 2019 and Differences in their Body Composition olo Players of Montenegro and Serbia who participated in the FINA World Junior Water Polo Championship 2019 and Differences in their Body Composition - Jovan Gardasevic; Dusko Bjelica; Ivan Vasiljevic; Marko Aleksandrovic; Tomislav Okicic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
This research aimed to determine the differences between the junior (U20) water polo players of national teams of Montenegro and Serbia in the anthropometric characteristics and body composition. The first sub-sample of the subjects consisted of 15 water polo players of the Serbian national team, the vice-champions of the FINA World Men's Junior Water Polo Championship in Kuwait 2019, and the second sub-sample consisted of 18 water polo players of the Montenegrin national team, who occupied the sixth position on the championship. The players were tested at the final preparations just before the World Championship in Kuwait in 2019. Anthropometric characteristics and body composition were evaluated using a battery of 11 variables: body height, body weight, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold, upper-leg skinfold, lower leg skinfold, body mass index, fat percentage, and muscle mass. Based on the results, it can be stated that the values of all the variables are highly similar to all of the water polo players of these two countries. The t-test found that the water polo players of the two national teams do not have statistically significant differences in the variables for assessing anthropometric characteristics and body composition. The results obtained in this research can serve as model parameters for the estimated variables for all water polo players (U20) in the World , because the players that have been analysed were the best and the most successful water polo players in their countries, and participants in the World Championship in Kuwait 2019.